2017
DOI: 10.3126/jpn.v7i2.18002
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of ovarian tumours- a five year study

Abstract: Background: Ovarian tumor is the seventh most common cause of cancer related deaths in female. The aim of this study is to find the, morphological and clinicopathological correlation, gross, histological pattern, and incidence of age distribution of ovarian tumors. Materials and Methods:This retrospective and prospective study was carried out from January 2011 to December 2015. The diagnosis was confirmed by histopathological examination using hematoxylin and eosin stain. Special stains and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…In surface epithelial tumour, Serous Cystadenoma was the most common benign neoplasm followed by Mucinous Cystadenoma. This finding coincided with previous studies by Gupta et al [32] Similar results have been reported by Yasmin et al and Narang et al [25,35] Teratoma was the most common Germ cell tumour found in our study contributing 18 cases (21.68%) of all ovarian tumours which is comparable to the results observed in studies carried out by Yasmin et al and Zaman et al Which were showing 18% and 19.35% respectively [25,36]. A single case of Brenner's tumour was also reported in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In surface epithelial tumour, Serous Cystadenoma was the most common benign neoplasm followed by Mucinous Cystadenoma. This finding coincided with previous studies by Gupta et al [32] Similar results have been reported by Yasmin et al and Narang et al [25,35] Teratoma was the most common Germ cell tumour found in our study contributing 18 cases (21.68%) of all ovarian tumours which is comparable to the results observed in studies carried out by Yasmin et al and Zaman et al Which were showing 18% and 19.35% respectively [25,36]. A single case of Brenner's tumour was also reported in our study.…”
Section: Discussionsupporting
confidence: 93%
“…20 (52.63%) out of 38, similar to the study findings by Gupta N et al, [3] The metastatic tumors constituted 2 (3.77%) cases, both being Krukenberg tumor which is in concordance with study by Garg N et al, [8] Bhagyalakshmi A et al, [13] Jha R et al, [14] and Gupta N et al, [15] . Majority of the benign tumors occurred in the younger age group and the malignant tumors were more common in older age group which is in concordance with the study conducted by Jha R et al, [14] Narang S et al, [16] and Shah S et al, [17] ~ 181 ~…”
Section: Discussionsupporting
confidence: 88%
“…Ovarian neoplasms (ONs) comprise 3% of all cancers [ 1 , 2 ], and among female genital tract-related malignancies, the incidence is 25% [ 3 , 4 ]. Ovarian cancer is the fifth most prevalent cancer overall and the second most common gynecological cancer [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%